2005
DOI: 10.1080/09645290500031199
|View full text |Cite
|
Sign up to set email alerts
|

Raising academic standards and vocational concentrators: Are they better off or worse off?

Abstract: This paper measures the impacts of tougher graduation requirements on course taking patterns, learning, college attendance and post high school labor market outcomes for vocational concentrators and nonconcentrators. Our main goal was to assess whether vocational education students were specifically affected (positively or negatively) by the policies heavy emphasis on the academic part of the high school curriculum. Our results show how requiring higher number of academic credits to graduate and introducing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Overall, the evidence described below indicates that youth completing school-based VET do as well (and sometimes better) than if they had instead remained in purely academic studies (Tansel 1994, 1999; Mane 1999; Tunali 2002; Bishop and Mane 2004, 2005; Meer 2007). Some evidence found that school-based VET is most efficient when the area of vocational training is matched with the occupation of employment, whereas no significant differences arise for unmatched groups (Neuman and Ziderman 1991, 1999).…”
Section: Empirical Evidencementioning
confidence: 94%
“…Overall, the evidence described below indicates that youth completing school-based VET do as well (and sometimes better) than if they had instead remained in purely academic studies (Tansel 1994, 1999; Mane 1999; Tunali 2002; Bishop and Mane 2004, 2005; Meer 2007). Some evidence found that school-based VET is most efficient when the area of vocational training is matched with the occupation of employment, whereas no significant differences arise for unmatched groups (Neuman and Ziderman 1991, 1999).…”
Section: Empirical Evidencementioning
confidence: 94%
“…The findings of this literature are overall quite mixed. Some papers (Mane, 1999;Bishop & Mane, 2005;Meer, 2007) have reported on a positive relationship between vocational secondary education and earnings. Citylevel, state-level, and national-level quasi-experimental studies commissioned by the US Department of Education as part of a national assessment of vocational education found more mixed evidence on the impact of vocational education on educational and labor market outcomes (US DOE, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In newer research, Dougherty (forthcoming) finds large high school graduation effects from students who are just accepted into career academies in Massachusetts compared with those who just miss the cutoff. Analyses using older cohorts have generally supported the same conclusions (Gustman & Steinmeier, 1982;Kang & Bishop, 1989;Bishop & Mane, 2005). Yet, selection is an issue in evaluating vocational programs and none of these studies use exogenous variation.…”
Section: Prior Workmentioning
confidence: 55%